(untitled) (Research, Society and Development, 2024)
Breast cancer (CA) is the malignant proliferation of cells located around the breast ducts and/or lobules, mainly affecting the upper external quadrant of the breast. It is considered the type of cancer that most affects women, with a high prevalence in all countries. According to the National Cancer Institute (INCA), in 2022 there were 66,280 new cases of breast cancer. The pathology behaves differently between patients and can present different clinical manifestations derived from histological and genetic variations. Currently, several histological types of breast cancer are known, with ductal/lobular in situ being the most common type of carcinoma, affecting only the mammary ducts/lobes. However, in cases of lack of diagnosis or treatment failure, breast CA can progress to an aggressive histological type, being invasive lobular/ductal carcinoma. Therefore, the present work has the general objective: Analyze the diagnosis of breast CA and the challenges encountered in the treatment, prognosis and tracking of the main histological types in Brazil, based on a systematic literature review. It can be concluded from the research that breast cancer is increasing in prevalence as a result of population aging and society’s lifestyle. Furthermore, it can be noted that screening is of great importance for the early start of treatment, thus avoiding more invasive procedures on the patient and a better prognosis.